Encouraging Positive Youth Video Game Activities - Rosemary V. Barnett (EDIS)
In todays world youth are increasingly using electronic media. School assignments include web-based research for homework, e-mail has replaced letter writing, and the convenience of instant messaging is starting to replace the telephone. Youth today are more media literate than their parents, yet the outcomes of this transition are not always positive. Youth recreation has merged with media to include video games, music downloading, and interactive websites, in many cases replacing traditional youth activities, such as basketball, swimming, or other outdoor recreation. This document is FCS2238, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 2005.